The “Dual Identity” of the Sovereign State and the Problem of Foundation in Global Politics - Goguen, Marcel R. (Université d'Ottawa / University of Ottawa, 2012)
Recently, many authors from various theoretical backgrounds have written books or articles trying to clarify what the role of the sovereign state is within the wider political context of “global politics.” This thesis seeks to critically engage with the way in which this debate has been framed by the vast majority of these authors. Indeed, while most authors frame this debate as an essentially empirical disagreement concerning the objective composition of global politics, we will be arguing that it is really a debate that concerns the problem of political foundation and the possibly changing nature of the dominant ways of answering this problem in contemporary “global politics.” From this perspective, the vast majority of those involved in this debate simply pass over - as somehow analytically uninteresting - most of the questions that would really need to be explained and understood. This thesis seeks to address this crucial oversight
Keywords: gouvernance; sovereignty; the state; global politics; International Relations Theory; foundation; globalization